1302. Antibiotic Prescribing Knowledge: A Brief Survey of Providers and Staff at an Ambulatory Cancer Center During Antibiotic Awareness Week 2017. (26th November 2018) - Stohs, Erica; Krantz, Elizabeth M; Sweet, Ania; Zier, Jacqlynn; Paleologos, Maria; Pergam, Steven A; Liu, Catherine
Abstract: Background: Antibiotics have contributed significantly to advances in cancer therapy and hematopoietic cell transplantation, but rising antibiotic resistance threatens this progress. Little is known about knowledge and perceptions surrounding antibiotic use and resistance among staff at cancer centers. Methods: We conducted a brief cross-sectional survey of healthcare professionals (HCP) at a large ambulatory cancer center to assess knowledge of antibiotic prescribing and resistance during Antibiotic Awareness Week, November 13–19, 2017. A convenience sample of providers and staff who participated in one of two 2-hour Antimicrobial Stewardship Program "open house" events was used. Questions evaluated knowledge about antibiotic use for upper respiratory tract infections (URIs). Results: There were 179 respondents. The proportion of correct responses to each question by employee type is displayed in Table 1. There was a statistically significant decreasing trend in the proportion correctly answering all four questions by employee type from providers, to pharmacists, to nurses, to others ( P <0.001) (Figure 1). Conclusion: Providers were more likely to correctly answer questions pertaining to antibiotic use compared with other HCP. Due to the multidisciplinary nature of cancer care, patients often encounter a variety of HCP over the course of treatment. Opportunities exist to improve antibiotic stewardship education across the spectrum of HCP at our cancer center, including pharmacists, nurses, and other staff. Disclosures: All authors: No reported disclosures.